Effect of Electronic Tax Invoice Adoption on Transparency of Indonesia Stock Exchange Main Board Companies - Dwi Joko Susilo; Khoirunurrofik (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
This study analyzes the relationship between adopting electronic tax invoice (ETI) and public companies' transparency. The analysis was conducted using binary panel data with a random-effects model, with data observations of companies listed on the Main Board of the Indonesia Stock Exchange except for the financial and technology sectors in the 2012-2019 period. The analysis results show that ETI affects the transparency of all three types of profits for a subsample of companies with enormous assets on the Main Board. Analysis of the industrial sector shows the industrial sectors of raw goods and secondary consumer goods have a significant influence. Furthermore, the findings of industrial sectors and certain types of profits where ETI has no considerable effect on transparency suggest the ETI application should improve its features. It will prevent transaction manipulation and company's behavior for making income smoothing. On the other hand, it is necessary to carry out a strategy of extracting tax potential for a particular sector related to fictitious invoice cases and frequent affiliate transactions.